2021
DOI: 10.1186/s12935-021-01968-y
|View full text |Cite
|
Sign up to set email alerts
|

hnRNPA2B1 regulates the alternative splicing of BIRC5 to promote gastric cancer progression

Abstract: Background Systematic profiling studies have implicated regulators of pre-mRNA splicing as important disease determinants in gastric cancer (GC), but the underlying mechanisms have remained elusive. Here we focused on hnRNPA2B1 splicing factor-dependent mechanisms governing GC development. Methods The expression of hnRNPA2B1 was analyzed among the Cancer Genome Atlas (TCGA) datasets of GC and validated at mRNA level. The function of hnRNPA2B1 in GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…At the same time, also studies have found that HNRNPA2B1 was the oncogenic gene in esophageal cancer(ESCA), the increased expression of HNRNPA2B1 could predict adverse prognosis of ESCA by affecting tumor-promoting signaling pathways, silencing HNRNPA2B1 could inhibit the proliferation of ESCA cells (Li et al, 2021). Also overexpression of HNRNPA2B1 is correlated with poor survival in gastric cancer (GC), multiple myeloma (MM) and ovarian cancer and HNRNPA2B1 acts as an oncogenic role in their progression (Yang et al, 2020;Jiang et al, 2021;Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…At the same time, also studies have found that HNRNPA2B1 was the oncogenic gene in esophageal cancer(ESCA), the increased expression of HNRNPA2B1 could predict adverse prognosis of ESCA by affecting tumor-promoting signaling pathways, silencing HNRNPA2B1 could inhibit the proliferation of ESCA cells (Li et al, 2021). Also overexpression of HNRNPA2B1 is correlated with poor survival in gastric cancer (GC), multiple myeloma (MM) and ovarian cancer and HNRNPA2B1 acts as an oncogenic role in their progression (Yang et al, 2020;Jiang et al, 2021;Peng et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, transcriptomic analysis of brain samples from 559 schizophrenia patients revealed that changes in the expression of transcript splice variants captured the largest schizophrenia effect [ 109 ]. In our data, endothelial nuclei derived from schizophrenia exhibited reduced expression of HNRNPA2B1 , a gene coding for a heterogeneous ribonucleoprotein involved in the alternative splicing of several genes [ 110 112 ] (S. Fig. 2D ).…”
Section: Discussionmentioning
confidence: 63%
“…In addition, transcriptomic analysis of brain samples from 559 schizophrenia patients revealed that changes in the expression of transcript splice variants captured the largest schizophrenia effect [6]. In our data, endothelial nuclei derived from schizophrenia depicted reduced expression of HNRNPA2B1, a gene coding for a heterogeneous ribonucleoprotein involved in the alternative splicing of several genes [111][112][113] (S. Figure 2D). However, as the 10X snRNAseq methodology does not allow for the detection of alternative spliced transcripts, our data do not contain alternative splicing information; thus, we cannot evaluate whether the reduced expression of HNRNPA2B1 in schizophrenia affects the transcriptome of endothelial nuclei at the isoform-level.…”
Section: Discussionmentioning
confidence: 53%